What future for urban environments in Europé : contribution to Habitat II: with interviews of Ministers of urban affairs in the European Union. (Office for Official Publications of the European Communities, 1996)
This publication constitutes the contribution of the Foundation to the Summit of Cities (Instabul, June 1996). It has been finalised after the contribution of a panel of high level experts and decision-makers who met in Dublin for the workshop on "Urban Innovations towards Habitat II" (28-29 March 1996). Part I of this publication includes interviews with Ministers of Urban Affairs in the European Union. Part II highlights from the Foundation's work on urban environment (1993-96). They are linked to Best Urban Practices and urban sustainability indicators, two themes at the very heart of the HABITAT II Agenda.